Differential-Evolution-Based Optimization of the Dynamic Response for Parallel Operation of Inverters With No Controller Interconnection - Godoy, Ruben Barros; Pinto, Joao O. P.; Canesin, Carlos Alberto [UNESP]; Alves Coelho, Ernane Antonio; Pinto, Alexandra M. A. C. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
In this paper, the use of differential evolution ( DE), a global search technique inspired by evolutionary theory, to find the parameters that are required to achieve optimum dynamic response of parallel operation of inverters with no interconnection among the controllers is proposed. Basically, in order to reach such a goal, the system is modeled in a certain way that the slopes of P-omega and Q-V curves are the parameters to be tuned. Such parameters, when properly tuned, result in system's eigenvalues located in positions that assure the system's stability and oscillation-free dynamic response with minimum settling time. This paper describes the modeling approach and provides an overview of the motivation for the optimization and a description of the DE technique. Simulation and experimental results are also presented, and they show the viability of the proposed method.
Keywords: dynamic response optimization; parallel operation of inverters; Differential evolution (DE)